2020
DOI: 10.1186/s13104-020-4919-3
|View full text |Cite
|
Sign up to set email alerts
|

Stability of neuropsychological test performance in older adults serving as normative controls for a study on postoperative cognitive dysfunction

Abstract: Objective: Studies of postoperative cognitive dysfunction (POCD) rely on repeat neuropsychological testing. The stability of the applied instruments, which are affected by natural variability in performance and measurement imprecision, is often unclear. We determined the stability of a neuropsychological test battery using a sample of older adults from the general population. Forty-five participants aged 65 to 89 years performed six computerized and noncomputerized neuropsychological tests at baseline and agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The test-retest reliability coefficients documented by Karlsen et al (2020) are broadly in keeping with reliability levels previously reported for CANTAB (Barnett et al, 2010;Cacciamani et al, 2018;Feinkohl et al, 2020;Fowler et al, 1995;Gonçalves et al, 2016;Lowe & Rabbitt, 1998). As noted by Karlsen et al (2020) themselves, test-retest reliability below r ¼ .75 is not unique to CANTAB but is commonly reported for many traditional neuropsychological measures.…”
Section: Commentsupporting
confidence: 81%
“…The test-retest reliability coefficients documented by Karlsen et al (2020) are broadly in keeping with reliability levels previously reported for CANTAB (Barnett et al, 2010;Cacciamani et al, 2018;Feinkohl et al, 2020;Fowler et al, 1995;Gonçalves et al, 2016;Lowe & Rabbitt, 1998). As noted by Karlsen et al (2020) themselves, test-retest reliability below r ¼ .75 is not unique to CANTAB but is commonly reported for many traditional neuropsychological measures.…”
Section: Commentsupporting
confidence: 81%
“…The ability to distinguish natural variability and measurement error from biologically relevant cognitive changes due to aging or early neurodegeneration is valuable to provide informed decisions on diagnosis, monitoring, and treatment of cognitive impairments (Feinkohl et al, 2020). However, older adults show more intraindividual variability in performance measures of working memory compared to younger adults.…”
Section: Introductionmentioning
confidence: 99%
“…The composition and retest reliabilities of the test battery are described in an additional publication. 21 Trained doctoral students and study nurses performed the testing based on a standard operating procedure, which was approved by two neuropsychologists.…”
Section: Methodsmentioning
confidence: 99%